Multifunctional Opioid-Derived Hybrids in Neuropathic Pain: Preclinical Evidence, Ideas and Challenges - Starnowska-Sokół, Joanna (Molecules, 2020)
When the first- and second-line therapeutics used to treat neuropathic pain (NP) fail to induce efficient analgesia—which is estimated to relate to more than half of the patients—opioid drugs are prescribed. Still, the pathological changes following the nerve tissue injury, i.a. pronociceptive neuropeptide systems activation, oppose the analgesic effects of opiates, enforcing the use of relatively high therapeutic doses in order to obtain satisfying pain relief. In parallel, the repeated use of opioid agonists is associated with burdensome adverse effects due to compensatory mechanisms that arise thereafter. Rational design of hybrid drugs, in which opioid ligands are combined with other pharmacophores that block the antiopioid action of pronociceptive systems, delivers the opportunity to ameliorate the NP-oriented opioid treatment via addressing neuropathological mechanisms shared both by NP and repeated exposition to opioids. Therewith, the new dually acting drugs, tailored for the specificity of NP, can gain in efficacy under nerve injury conditions and have an improved safety profile as compared to selective opioid agonists. The current review presents the latest ideas on opioid-comprising hybrid drugs designed to treat painful neuropathy, with focus on their biological action, as well as limitations and challenges related to this therapeutic approach.